2020
DOI: 10.1017/aer.2019.160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of new aircraft separation minima on available airspace capacity and arrival time delay

Abstract: Although the application of new, reduced aircraft separation minima can directly increase runway throughput, the impact thereof on the traffic flow of aircraft arriving at the destination airport has not been discussed yet. This paper proposes a data-driven and queue-based modeling approach and presents an analysis of the impact on the delay time of arriving aircraft in the airspace within a radius of 100 nautical miles around an airport. The parameters of our queuing model were estimated by analysing the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…In (15) an M /G/c queuing model is proposed to analyze air traffic in an airspace around an airport. In (16), a discussion on future air traffic control strategies is provided. In (18), a state dependent M /M /c/K queuing model is applied to control the pedestrian flows and the capacity of pedestrian facilities in open outdoor walking environments.…”
Section: Introductionmentioning
confidence: 99%
“…In (15) an M /G/c queuing model is proposed to analyze air traffic in an airspace around an airport. In (16), a discussion on future air traffic control strategies is provided. In (18), a state dependent M /M /c/K queuing model is applied to control the pedestrian flows and the capacity of pedestrian facilities in open outdoor walking environments.…”
Section: Introductionmentioning
confidence: 99%
“…6(1)) and 30 aircraft (see Fig. 6(2)) from the south-west arrives within 150NM radius concentric circle in an hour [12].…”
Section: Shifting Air Traffic Control Flow To Time-based Traffic Managementmentioning
confidence: 96%
“…One of the important arrival strategies to determine is where and how the aircraft arrival flow shifts to time management towards the arrival airport while minimizing arrival delay time. The first author's study clarified the best arrival strategy based on the analysis applying data-driven queuing models [10][11] [12]. The proposed queue-based approach demonstrated that there are five parameters, which impact on arrival delay time as follows: 1) arrival traffic rate 2) airspace capacity 3) mean of aircraft flight time 4) variance of aircraft flight time 5) variance of aircraft inter-arrival time.…”
Section: Shifting Air Traffic Control Flow To Time-based Traffic Managementmentioning
confidence: 99%
See 2 more Smart Citations